Pengembangan Komunitas Entrepreneur Berbasis Social Entrepreneurship Melalui Program Greenthink - Moh Syaiful Suib; Habibatur Rizkiyah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The abundance of marine catches with low selling prices is the cause of the decline in people's income levels. The entrepreneurial community based on social entrepreneurship is one of the solutions in solving the social and economic problems of the community. This study aims to find out about the development carried out in the entrepreneurial community based on social entrepreneurship through the Greenthink program. Data collection techniques were carried out through observation, interviews and documentation, the research was analyzed through a descriptive qualitative approach. The results of this study indicate that the process of developing an entrepreneurial community based on social entrepreneurship through the greenthink program is carried out through several stages of assistance starting from product manufacturing training, product packaging and product marketing accompanied by continuous improvements as upgrading in running a business and to create a fish processing center in Indonesia. Probolinggo Regency. The development carried out through the greenthink program has succeeded in making the entrepreneurial community of the Karanganom assisted group experience a fairly good development in terms of the quality of human resources and the business they run. Keywords: Entrepreneur, Social Entrepreneur, Greenthink